Kinetic study and modeling of bioethanol production from sago hydrolyzate in pilot scale bioreactor - Mohd Hider bin Kamarudin (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Kinetic and modeling approach was considered to be an essential step in developing a more efficient fermentation process. In this work, two fermentations were performed in 15 L and 150 L working volume bioreactors and the result for both fermentations were compared. Biomass, glucose and ethanol concentrations were measured at 4 h time interval during fermentation. Initial glucose concentrations were 141 g/L and 208 g/L for 15 L and 150 L fermentation respectively. Maximum ethanol concentration obtained was 55.3 g/L and 83.6 g/L for 15 L and 150 L fermentation respectively. Maximum biomass concentration achieved was 6.08 g/L and 8.4 g/L for 15 L and 150 L fermentation respectively. Product yield for 15 L and 150 L fermentation were YP/S = 0.4295 g/g and YP/S = 0.4806 g/g which represents 84% and 94% of the percentage yield from the theoretical maximum value respectively. Kinetics of ethanol fermentation from sago starch hydrolyzate using Saccharomyce cerevisiae was studied. Kinetic parameters were determined from the experimental data using slope calculating method and estimated from the kinetic models. Estimated values of the kinetic parameters for 15 L fermentation were µmax = 0.091 h-1, Xm = 6.03 g/L, ∆t = 35.64 h-1, m = 0.118 g/g h, YX/S = 0.085 g/g and YP/X = 11.3 g/g. Estimated values of the kinetic parameters for 150 L fermentation were µmax = 0.125 h-1, Xm= 8.264 g/L, ∆t = 9.803 h-1, m = 0.14 g/g h, YX/S = 0.079 g/g and YP/X = 10.432 g/g. The experimental data were fitted using non-linear regression method via simulation using Microsoft Excel 2010 together with method of statistical analysis for error minimization. Logistic model, substrate consumption and growth associated product formation with lag time parameter model were chosen as the best models able to fit the experimental data accordingly.